2016
DOI: 10.1021/acs.energyfuels.6b00419
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Evaluation of Petroleum Demulsifiers of Multibranched Block Copolymers

Abstract: A series of multibranched block copolymers was synthesized by means of anionic ring opening polymerization (AROP) techniques, using different alkoxide salts obtained from molecules that present different numbers of alcohol functions as initiators. Propylene oxide (PO) and ethylene oxide (EO) were polymerized in two steps, with the intent of obtaining multibranched block copolymers (PO/EO) with demulsifying activity in petroleum. The characterization of the polymers was done by means of size exclusion chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Copolymers with amphiphilic properties can be used in a wide range of applications including thin-film nanopatterning, 13 bottom-up nanofabrication, 47 demulsifying and antifoaming in extraction methods, 810 drug delivery, 11 and protein encapsulation. 12,13 In bulk water conditions, the solvation and dissociation of charged macromolecules favors solubilization, unless multivalent ions 14 or oppositely charged macroions 15 are added in the system, and dominates the assembly of charged containing copolymers in low monovalent salt conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copolymers with amphiphilic properties can be used in a wide range of applications including thin-film nanopatterning, 13 bottom-up nanofabrication, 47 demulsifying and antifoaming in extraction methods, 810 drug delivery, 11 and protein encapsulation. 12,13 In bulk water conditions, the solvation and dissociation of charged macromolecules favors solubilization, unless multivalent ions 14 or oppositely charged macroions 15 are added in the system, and dominates the assembly of charged containing copolymers in low monovalent salt conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Copolymers with amphiphilic properties can be used in a wide range of applications including thin-film nanopatterning, bottom-up nanofabrication, demulsifying and antifoaming in extraction methods, drug delivery, and protein encapsulation. , In bulk water conditions, the solvation and dissociation of charged macromolecules favors solubilization, unless multivalent ions or oppositely charged macroions are added in the system, and dominates the assembly of charged containing copolymers in low monovalent salt conditions . In organic media, on the other hand, ionic correlations in charge-containing copolymers lead to the formation of ionic clusters. The ionic clusters can lead to nontrivial thermodynamic changes in the molten state, such as the evolution of inverted phases, , and ion-dependent miscibility of ion-conducting block copolymers .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on an offshore platform showed that the aging oil emulsions daily produced contain ∼288 to ∼400 m 3 of water, accounting for more than half of the total water content of crude oil transported out of the platform. The huge volume of emulsified water increases the cost of oil storage and transport and leads to significant corrosion of pipelines and other equipment . Therefore, it is necessary to carry out further demulsification of aging oil emulsions on the offshore platform prior to their transport.…”
Section: Introductionmentioning
confidence: 99%
“…The huge volume of emulsified water increases the cost of oil storage and transport and leads to significant corrosion of pipelines and other equipment. 7 Therefore, it is necessary to carry out further demulsification of aging oil emulsions on the offshore platform prior to their transport.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical demulsification is a reliable and highly efficient technique to accelerate the separation of oil and water . Demulsifiers most commonly used today in the oil industry are amphiphilic compounds containing both hydrophilic and hydrophobic moieties within the same molecule, such as copolymers of poly(ethylene oxide‐ b ‐propylene oxide) (PEO‐ b ‐PPO), polyoxyalkylated epoxy resins, polyoxyalkylated alkyl‐phenol‐formaldehyde resins, polyoxyalkylated amines, polyoxyalkylated glycols, polyethyleneimines, dendrimer types, and mixtures of them copolymer . Effective demulsifiers can change the interfacial rheological properties, lower the interfacial tension, and quicken the thinning rate of interfacial film, promote coalescence of water droplets, thereby destabilizing the emulsions …”
Section: Introductionmentioning
confidence: 99%